Anti‐diabetic drugs and sarcopenia: emerging links, mechanistic insights, and clinical implications. Issue 6 (21st October 2021) - Zhang, Xueli; Zhao, Yi; Chen, Shuobing; Shao, Hua
Abstract: Sarcopenia, characterized by loss of skeletal muscle mass, quality, and strength, has become a common hallmark of ageing and many chronic diseases. Diabetes mellitus patients have a higher prevalence of sarcopenia, which greatly aggravates the metabolic disturbance and compromises treatment response. Preclinical and clinical studies have shown differential impacts of anti‐diabetic drugs on skeletal muscle mass, strength, and performance, highlighting the importance of rational therapeutic regimen from the perspective of sarcopenia risk. In this review, we provide an update on the regulation of muscle mass and quality by major anti‐diabetic drugs, focusing primarily on emerging data from clinical studies. We also discuss the underlying mechanisms and clinical implications for optimal selection of anti‐diabetic drugs to reduce the risk of sarcopenia. In view of the lifelong use of anti‐diabetic drugs, we propose that a better understanding of the sarcopenia risk and interventional strategies is worthy of attention in future studies.